The Impact of Loneliness on Electronic Cigarette use Among Adolescents: A Scoping Review - Zulkifli Zulkifli; Nur Setiawati Dewi; Megah Andriany (Indonesian Journal of Global Health Research, 2024)
Loneliness is increasingly recognised as a significant factor affecting adolescent health behaviours. Recent studies have indicated a potential link between feelings of loneliness and the rise in electronic cigarette (e-cigarette) usage among teenagers. This scoping review aims to systematically explore and synthesize the literature regarding the influence of loneliness on e-cigarette use among adolescents, identifying gaps and areas for further research. A comprehensive literature search was conducted following the PRISMA-ScR guidelines. Databases such as PubMed, Scopus, and Web of Science were utilised to locate peer-reviewed articles published in the last 10 years. Inclusion criteria focused on studies discussing loneliness and e-cigarette use among adolescents. Data extraction involved thematic analysis to identify recurring themes and outcomes. Preliminary findings indicate a positive correlation between feelings of loneliness and increased e-cigarette consumption in adolescents. The review highlights various psychosocial factors, including peer influence and mental health, contributing to this trend. The findings underscore the importance of addressing loneliness as a critical determinant in the promotion of e-cigarette use among youth. Future interventions should consider targeting social connectedness to mitigate the impact of loneliness on health behaviours.